Engineered bacterial membrane biomimetic covalent organic framework as nano-immunopotentiator for cancer immunotherapy - Qi-Chao Yang; Yuan-Yuan Wang; Shuo Wang; An Song; Wen-Da Wang; Liang Zhang; Zhi-Jun Sun (Bioactive Materials)
The cellular uptake and tissue dispersion efficiency of nanomedicines are crucial for realizing their biological functionality. As a cutting-edge category of nanomedicine, covalent organic frameworks (COFs)-based photosensitizers, have been extensively employed in cancer phototherapy in recent years. However, the inherent aggregation tendency of COFs hinders their uptake by tumor cells and dispersion within tumor tissues, thereby limiting their therapeutic efficacy. In this study, we employed Fusobacterium nucleatum (F.n.), a prevalent intratumoral bacterium, to construct a bacterium membrane-wrapped COF, COF-306@FM, which is readily taken up by cancer cells and uniformly dispersed within tumor tissues. Meanwhile, the F.n. membrane can also serve as an immune adjuvant to warm up the “cold” tumor immune microenvironment by enhancing the CD8+ T and B cells infiltration, and inducing the formation of tumor-located tertiary lymphoid structures. Consequently, the response rate of αPD-L1 immunotherapy was drastically promoted to efficiently prevent tumor metastasis and recurrence, causing 84.6 % distant tumor inhibition and complete suppression of tumor metastasis. In summary, this innovative approach not only enhances the therapeutic potential of COFs but also opens up new avenues for integrating microbial and nanotechnological strategies in cancer treatment.